Mitigation of voltage SAG using PWM switched autotransformer / Nur Fadhilah Jamaludin - Jamaludin, Nur Fadhilah (2011)
Power quality disturbances especially voltage sag become significant issues which make many researchers to be interested to find the effective solutions to solve it. According to this problem, there are few mitigation device that have been introduced such as dynamic voltage restorer (DVR) and distribution static compensator (DSTATCOM) in order to mitigate the voltage sag disturbances. However in this study, the objective of this project is to analyze the effectiveness of pulse width modulation (PWM) switched autotransformer as mitigation device for various percentages of voltage sag due to three phase fault with the total harmonic distortion (THD) of load voltage within the limits when the compensator is functioning. This research will be simulated by using PSCAD/EMTDC software. The simulation results of PWM switched autotransformer are presented. The results show that the effectiveness of the compensator as mitigation devices in order to maintain the THDs of load voltage within the limit during various percentages of voltage sag disturbances. It was also shown that because of detection delay, there exists an output voltage overshoot transient at the moment of the recovery voltage where will be increase as the magnitude of voltage sag decrease.